Russia, Ukraine, Belarus in the program documents of the three governments of Angela Merkel (2005– 2017) - Froltsov, Vladislav V. (Journal of the Belarusian State University. International Relations, 2018)
The article traces the evolution of assessments of the role of Russia, Ukraine and Belarus as the most important partners of Germany in Eastern Europe in the system of the regional priorities of the German foreign policy basing on the content of the program documents of the three Angela Merkel’s governments: 2005, 2009 and 2013 Coalition Agreements and 2006 and 2016 “White Papers on German security policy and the future of the Bundeswehr”. As a result, the most significant changes in the vision of the German interests in Eastern Europe, which occurred during Angela Merkel’s chancellorship and can exert a decisive influence on the future German foreign policy, were revealed.